Possessivi e nomi di parentela in alcune varietà italiane antiche e moderne - Penello, Nicoletta (Verbum – Analecta Neolatina, 2002)
In this paper I will discuss the syntax of possessives cooccurring with Kinship Nouns in Old Italian and Old Venetian in comparison with modern italian varieties. Considering the morphology of possessives and the semantics of the class of Kinship Nouns I will try to explain why this class of nouns displays - in different varieties - a peculiar syntactic behaviour with regard to the cooccurrence of possessives and definite articles.